POST-WAR ECONOMIC RECONSTRUCTION AND FOREIGN ECONOMIC RELATIONS IN UZBEKISTAN (1946–1953) (The Conference Hub, 2025)
This article analyzes the economic reforms implemented in Uzbekistan within the framework of the fourth five-year plan of 1946–1953. The main attention was paid to the restoration of industry, the development of agriculture and the expansion of the education sector. At the same time, the republic increased its export potential by activating foreign economic relations. The analysis shows that during this period the republic's economy developed rapidly. The topic deeply covers the post-war recovery processes of Uzbekistan.